Skilled Service and Women's Work: Canadian Nursing, 1920-1939 - McPherson, Kathryn Mae (Simon Fraser University, 1989)
This thesis examines the experiences, attitudes and actions of the women who trained and worked as graduate nurses during the 1920-1939 years--of the third generation of hospital-trained Canadian nurses. The 1920s and 1930s were decades of crisis for Canadian nursing, and the occupation's majority, working in the private duty sector, was most severely affected by the problems of oversupply and underemployment. The economic crisis was national in scope, and endemic to the health care system, and was therefore exacerbated rather than created by the depression of the 1930s. In order to analyze the structure and content of the occupation during these years of crisis, a wide variety of national sources were consulted, supplemented by a detailed case study of nursing in the prairie metropolis of Winnipeg, Manitoba. This research on Canadian nursing during the 1920s and 1930s adds another chapter to the growing scholarly literature on Canadian women and work. It also contributes to the secondary literature on the social history of medicine and of labour in two particular ways. First, as the largest health care workforce, the actions of graduate nurses during the 1920s and 1930s, their agency, served as a critical, force within the development of the Canadian health care system, a force frequently overlooked within medical history. Secondly, the third generation of Canadian nurses borrowed from the organizational strategies of both professionals and trade unions, but neither concept fully captured the reality of nurses' occupational identity as women and as workers. This thesis argues that the third generation of Canadian nurses was recruited from sex-segregated female labour market. The many rituals and routines which constituted nursing technique were based on a theoretical understanding and practical application of the germ theory. As such, nursing practice during the interwar years must be defined as scientific. Nurses' scientific skills permitted practioners to integrate caring and curing, and thereby to create their own definition to what constituted skilled service. Out of this self-definition came a specific occupational identity which was reflected in the many associations designed to reflect nurses' interests. As the interwar decades progressed, conflict developed within nursing organizations as to appropriate solutions to the economic crisis. The compromise solution, hospital employment of graduate nurses, initiated the demise of both the apprenticeship system of hospital staffing, and private duty nursing. This solution successfully prevented the fracturing of nursing organizations in the 1920s and 1930s, but also facilitated the transformation of hospital staffing which would occur in the World War II years. This research suggests that the scholarly literature on professionalism, and on labour organizations, must more fully account for gender as a historical determinant. In suggesting a historical periodization for Canadian nursing history, and in focussing on the third generation of Canadian nurses who struggled through the economic crisis of the interwar decades, this thesis contributes to the growing body of scholarly literature dedicated to placing nursing history in history.